Deposition of Major and Trace Elements From Atmosphere Over Baghdad During the Year of 2010. - AL-Rasoul, K.; Ali, F.; Jubair, S.; Ali, Q.; Najim, A.; Hussain, M.; Ahmed, F. (Iraqi Journal of Science, 2024)
Dust Samples depositions over Baghdad, from January to December 2010 were collected. The minerals and the concentration of both light elements (P, S, K, Ti, Mg, Ca, Si, Na, Al, and Fe) and heavy traces elements (Zn, Mn, Cu, Pb, Cr, Ni, As, Sr, Rb, and Co) were measured by using x-ray diffraction and fluorescence respectively. The minerals detected by x-ray diffraction were quartz, calcite, clay, gypsum, feldspar, chloride, and plagioclase. The average range for heavy elements are highly compared with the neighbor countries and similar or less than those reported for other urban worldwide, except for Ni,As,Cr,and Sr which record the highest comparing with other countries. The pH of dust was shifted to alkalinity for all samples with mean value of 8.5.